1989
DOI: 10.3109/07357908909038279
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Distribution of Diacetyl Didemnin B in Human Blood Cells and Plasma

Abstract: We have utilized [3H]diacetyl-didemnin B ([3H]DB) in a series of in vitro experiments to determine the time course of equilibration of [3H]DB between plasma and blood cells, the distribution of [3H]DB among blood cells, and the distribution of [3H]DB in plasma. Within 45-60 min at 37 degrees C, approximately 55% of [3H]DB added to whole blood remained in the plasma. Of the drug associated with blood cells, 77% was found with the red blood cells, 18% with the lymphocytes, and 5% with the granulocytes. However, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1992
1992
2002
2002

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…49 LeGrue was also able to corroborate earlier work showing that didemnin B exhibits a preference for S-phase cells, suggesting a possible therapeutic application against rapidly proliferating lymphocyte or tumor cells. Phillips et al 115 used a tritiated diacetyl didemnin B derivative to show that drug uptake per cell was much higher in lymphocytes than other cells.…”
Section: B Antiproliferative Activity and Protein Biosynthesis Inhibmentioning
confidence: 99%
“…49 LeGrue was also able to corroborate earlier work showing that didemnin B exhibits a preference for S-phase cells, suggesting a possible therapeutic application against rapidly proliferating lymphocyte or tumor cells. Phillips et al 115 used a tritiated diacetyl didemnin B derivative to show that drug uptake per cell was much higher in lymphocytes than other cells.…”
Section: B Antiproliferative Activity and Protein Biosynthesis Inhibmentioning
confidence: 99%
“…These authors and Hartshorn et al have used high performance liquid chromatography (HPLC) systems with detection limits of 50 m g / d (12) and 5 ng/ml, respectively (13). Dorr et al also reported the development of a radioimmunoassay (RIA) with a detection limit of 20 pg/ml (12,14); however, the antiserum required for this assay may no longer be available (Jason Fisherman, NCI, personal communication, 1990). In this study, didemnin haptens were synthesized and coupled to protein carriers for use as immunogens, and as solid phase coating antigen in enzyme-linked immunosorbent assay (ELISA) systems with anti-didemnin antibodies.…”
Section: Introductionmentioning
confidence: 99%